2014
DOI: 10.1111/ajco.12168
|View full text |Cite
|
Sign up to set email alerts
|

Predictors in breast cancer screening behaviors of South Asian women

Abstract: Five statistically significant predictors of mammographic screening among Sri Lankan women were identified. These suggest that higher health awareness and exposure to health care providers are important predictors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The current study showed a significant association between menopause and utilization of MS. This finding is consistent with Perera et al, (24) that found postmenopausal women to be more likely to undergo MS than premenopausal women.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The current study showed a significant association between menopause and utilization of MS. This finding is consistent with Perera et al, (24) that found postmenopausal women to be more likely to undergo MS than premenopausal women.…”
Section: Discussionsupporting
confidence: 93%
“…It was also in line with Vyas et al, (23) who reported that women aged 40 -49 years may be less likely to be adherent to MS than women aged 50 years and above. Another study conducted by Perera et al, (24) among Asian women revealed a similar finding: older women tended to use MS services more often. Concerning marital status, the study findings indicated that there was no significant association between MS utilization and marital status.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…We also hypothesize that other confounding factors such as level of education of partners, family income, permanent employment, having a relative affected by cancer will also be associated with better awareness and positive health seeking behaviours of females. It has been shown previously that better education, age greater than 50 years, past history of hysterectomy and several other factors to be significantly associated with attending breast cancer screening in Sri Lanka [ 5 ]. However, this sample was selected from women attending a mammography centre and is not representative of the community.…”
Section: Introductionmentioning
confidence: 99%